(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The selection of an appropriate surgical approach in obstructive jaundice—endoscopic sphincterotomy, percutaneous transhepatic drainage, biliodigestive anastomosis, or pancreatoduodenectomy—fundamentally depends on accurate preoperative anatomical characterization of the obstruction. Magnetic resonance cholangiopancreatography (MRCP), as a non-invasive high-resolution technique, provides precise visualization of the biliary tree and pancreatic duct without radiation exposure or procedural risk. However, data on the impact of MRCP-guided algorithms on treatment outcomes in local clinical settings remain limited. Evaluation of the clinical efficacy of an MRCP-based decision-making algorithm represents an important research objective